The Breeding of Sugarcane in Brazil and the Challenge of Global Climate Change (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.4909.22-46.Faced the challenges posed by climate change, Brazil needs to promote sustained growth of the sugarcane production to meet the growing demand. The expansion of production depends on the development of sugarcane varieties adapted to the soil and climate of the new areas of expansion. The national sugarcane sector has institutions historically responsible for the advances in technological development and innovation in the sector. Therefore, the identification of the main technological challenges that these institutions have found in their improvement programs is vital so that Brazil is able to maintain the leadership in sugarcane production. It was verified that, despite the existing technological capabilities, the challenges posed by new climatic conditions and changes in industry regulation impose limitations that must be overcome: the time of placement of a variety on the market; difficulties of internal infrastructure; difficulties in transmission of knowledge to producers; lack of government support; genetic complexity of plant cane sugar, among others.